Electrode assembly for lithium secondary battery and lithium secondary battery including the same

CN115989609BActive Publication Date: 2026-10-20LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280005796.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-26
Filing Date
2022-05-06
Publication Date
2026-10-20
Estimated Expiration
2042-05-06

AI Technical Summary

Technical Problem

[0006]然而,虽然LiCoO2由于其优异的物理性质如优异的循环特性而目前被广泛使用,但是其安全性低,并且LiCoO2由于作为原料的钴的资源限制而昂贵,因此在包括EV的领域中作为电源大量使用受到限制

Benefits of technology

[0031]根据本发明的锂二次电池用电极组件,通过将正极混合物层和负极混合物层中分别包含的正极添加剂和作为负极活性材料的含硅(Si)材料的含量百分比之间的比率(CRLip/CRSi)控制在特定范围内,具有以下优点:在初始充电/放电期间能够实现高充电/放电容量和充电/放电效率,在随后的充电/放电期间容量保持率可以是优异的,并且包括该电极组件的锂二次电池可以表现出高能量密度和长寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004097065950000121
    Figure GDA0004097065950000121
  • Figure GDA0004097065950000131
    Figure GDA0004097065950000131
  • Figure GDA0004097065950000141
    Figure GDA0004097065950000141
Patent Text Reader

Abstract

The present invention relates to an electrode assembly for a lithium secondary battery and a lithium secondary battery including the same. By controlling a ratio (CR Lip / CR Si ) between a content percentage of a positive electrode additive included in a positive electrode mixture layer and a negative electrode mixture layer, respectively, and a silicon (Si)-containing material as a negative electrode active material within a certain range, the electrode assembly can achieve high charge / discharge capacity and charge / discharge efficiency during initial charge / discharge, and excellent capacity retention rate during subsequent charge / discharge. The lithium secondary battery including the electrode assembly can exhibit high energy density and long life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to electrode assemblies for lithium secondary batteries and lithium secondary batteries including the same.

[0002] This application claims priority to Korean Patent Application No. 10-2021-0067353, filed on May 26, 2021, the entire contents of which are incorporated herein by reference. Background Technology

[0003] Recently, with increasing attention to environmental issues, research has been conducted on electric vehicles (EVs) and hybrid electric vehicles (HEVs) that can replace fossil fuel vehicles, such as gasoline and diesel vehicles, which are one of the main causes of air pollution. Although nickel-metal hydride (Ni-MH) secondary batteries are mainly used as power sources for EVs and HEVs, the use of lithium secondary batteries, which have high energy density, high discharge voltage, and output stability, is being actively researched, and some lithium secondary batteries have been commercialized.

[0004] Graphite is primarily used as the anode material in lithium-ion batteries. However, due to its low capacity of 372 mAh / g, it is difficult to achieve high capacities in lithium-ion batteries. Therefore, to achieve high capacities in lithium-ion batteries, anode materials that form intermetallic compounds with lithium, such as silicon, tin, and their oxides, have been developed and used as non-carbon-based anode materials with higher energy densities than graphite. However, the problem with these non-carbon-based anode materials is that, despite their high capacity, they have low initial efficiency, resulting in significant lithium consumption during the initial charging and discharging phases and substantial irreversible capacity loss.

[0005] In addition, lithium-containing cobalt oxide (LiCoO2) is mainly used as the positive electrode material for lithium secondary batteries. Besides LiCoO2, lithium-containing manganese oxides, such as LiMnO2 with a layered crystal structure or LiMn2O4 with a spinel crystal structure, and lithium-containing nickel oxide (LiNiO2) are also considered.

[0006] However, while LiCoO2 is currently widely used due to its excellent physical properties, such as superior cycling performance, its low safety and high cost due to the limited availability of cobalt as a raw material restrict its widespread use as a power source, including in electric vehicles. Furthermore, the characteristics of LiNiO2 manufacturing methods make it difficult to apply LiNiO2 to practical mass production processes at a reasonable cost, and the generation of gases during charging and discharging causes lithium plating on the negative electrode, resulting in reduced charging and discharging capacity and safety limitations.

[0007] [Existing Technical Documents]

[0008] [Patent Literature]

[0009] Korean Patent Application Publication No. 10-2018-0023696 Summary of the Invention

[0010] [Technical Issues]

[0011] The purpose of this invention is to provide a lithium secondary battery with high energy density and excellent battery life.

[0012] [Technical Solution]

[0013] This invention aims to solve the above-mentioned problems and provide an electrode assembly for a lithium secondary battery. The electrode assembly includes: a positive electrode, wherein a positive electrode mixture layer comprises a positive electrode active material and a positive electrode additive represented by the following chemical formula 1; a negative electrode, wherein a negative electrode mixture layer comprises a carbon material and a silicon-containing (Si) material as the negative electrode active material; and a separator located between the positive electrode and the negative electrode; wherein, based on 100 parts by weight of the positive electrode mixture layer, the content of the positive electrode additive is 0.01 to 5 parts by weight, and the percentage of the positive electrode additive based on the total weight of the positive electrode mixture layer (CR) is... Lip The percentage of Si-containing material based on the total weight of the negative electrode mixture layer (CR) Si The ratio between (CR) Lip / CR Si The value ranges from 0.03 to 0.30.

[0014] [Chemical Formula 1]

[0015] Li p Co (1-q) M 1 q O4

[0016] In chemical formula 1, M 1 It means that at least one element is selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.

[0017] In this case, the positive electrode additive is based on the percentage of content (CR) of the total weight of the positive electrode mixture layer. Lip The percentage of Si-containing materials based on the total weight of the negative electrode mixture layer (CR) Si The ratio between (CR) Lip / CR Si The value can range from 0.05 to 0.20.

[0018] The positive electrode additive may have a tetragonal structure with a space group of P4₂ / nmc.

[0019] The positive electrode active material may be a lithium metal composite oxide represented by the following Chemical Formula 2.

[0020] [Chemical Formula 2]

[0021] Li x [Ni y Co z Mn w M 2 v O u

[0022] In Chemical Formula 2, M 2 represents at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and x, y, z, w, v and u are respectively 1.0≤x≤1.30, 0≤y<0.95, 0<z≤0.5, 0<w≤0.5, 0≤v≤0.2 and 1.5≤u≤4.5.

[0023] The carbon material may include one or more selected from the group consisting of natural graphite, artificial graphite, graphene and carbon nanotubes, and the Si-containing material may include one or more of Si, silicon monoxide (SiO) and silicon dioxide (SiO₂).

[0024] Based on 100 parts by weight of the total amount of the carbon material, the carbon material may include one or more of graphene and carbon nanotubes in an amount of 0.1 to 10 parts by weight.

[0025] The positive electrode mixture layer may include 0.1 to 5 parts by weight of a conductive material based on the total weight.

[0026] The positive electrode mixture layer may contain one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fibers.

[0027] The average thickness of the positive electrode mixture layer may be 50 μm to 300 μm, and the average thickness of the negative electrode mixture layer may be 100 μm to 300 μm.

[0028] The average area ratio of the negative electrode mixture layer to the positive electrode mixture layer may be 1.0 to 1.1.

[0029] The present invention aims to solve the above problems and provides a lithium secondary battery including the above electrode assembly.

[0030] [Advantageous Effects]

[0031] According to the electrode assembly for lithium secondary batteries of the present invention, the ratio (CR) between the percentage content of the positive electrode additive and the silicon (Si) material as the negative electrode active material contained in the positive electrode mixture layer and the negative electrode mixture layer, respectively, is used. Lip / CR Si Controlling the capacity within a specific range has the following advantages: high charge / discharge capacity and charge / discharge efficiency can be achieved during the initial charge / discharge period, excellent capacity retention can be achieved during subsequent charge / discharge periods, and lithium secondary batteries including this electrode assembly can exhibit high energy density and long lifespan. Detailed Implementation

[0032] This invention can be modified in various forms and can have various implementation schemes; therefore, specific implementation schemes will be described in detail.

[0033] However, the embodiments should not be construed as limiting the invention to a particular embodiment, but should be interpreted as including all modifications, equivalents or alternatives that fall within the spirit and technical scope of the invention.

[0034] In this invention, the terms "comprising," "having," etc., are used to specify the presence of the features, numbers, steps, operations, components, elements, or combinations thereof described herein, and they do not exclude the presence or addition of one or more other features, numbers, steps, operations, components, elements, or combinations thereof.

[0035] Furthermore, in this invention, when a portion of a layer, film, region, plate, etc., is described as being "on" another portion, this includes not only the case where the portion is "directly" "on" the other portion, but also the case where other portions exist between the portion and the other portion. Conversely, when a portion of a layer, film, region, plate, etc., is described as being "below" another portion, this includes not only the case where the portion is "directly" "below" the other portion, but also the case where other portions exist between the portion and the other portion. Additionally, in this application, "deposited on" can include not only being disposed on the upper part but also being disposed on the lower part.

[0036] The invention will be described in more detail below.

[0037] Electrode assemblies for lithium secondary batteries

[0038] In one embodiment, the present invention provides an electrode assembly for a lithium secondary battery, the electrode assembly comprising: a positive electrode, wherein a positive electrode mixture layer comprises a positive electrode active material and a positive electrode additive represented by the following chemical formula 1; a negative electrode, wherein a negative electrode mixture layer comprises a carbon material and a silicon-containing (Si) material as the negative electrode active material; and a separator located between the positive electrode and the negative electrode; wherein, based on 100 parts by weight of the positive electrode mixture layer, the content of the positive electrode additive is 0.01 to 5 parts by weight, and the percentage of the positive electrode additive based on the total weight of the positive electrode mixture layer (CR) Lip The percentage of Si-containing material based on the total weight of the negative electrode mixture layer (CR) Si The ratio between (CR) Lip / CR Si The value ranges from 0.03 to 0.30.

[0039] [Chemical Formula 1]

[0040] Li p Co (1-q) M 1 q O4

[0041] In chemical formula 1, M 1 It means that at least one element is selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.

[0042] The electrode assembly for a lithium secondary battery of the present invention has a structure comprising a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes. In this case, the positive electrode has the form in which a positive electrode mixture layer is located on a positive electrode current collector, and the positive electrode mixture layer comprises a positive electrode active material exhibiting activity and a positive electrode additive imparting irreversible capacity. Specifically, the positive electrode active material is a positive electrode active material that can be reversibly intercalated and deintercalated, and may comprise a lithium metal composite oxide represented by the following chemical formula 2 as a main component:

[0043] [Chemical Formula 2]

[0044] Li x [Ni y Co z Mn w M 2 v ]O u

[0045] In chemical formula 2, M 2represents at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and x, y, z, w, v and u are respectively 1.0≤x≤1.30, 0≤y<0.95, 0<z≤0.5, 0<w≤0.5, 0≤v≤0.2 and 1.5≤u≤4.5.

[0046] The lithium-metal composite oxide represented by Chemical Formula 2 is a composite metal oxide containing lithium and nickel, and the composite metal oxide may include at least one compound selected from the group consisting of LiCoO₂, LiCo 0.5 Zn 0.5 O₂, LiCo 0.7 Zn 0.3 O₂, LiNiO₂, LiNi 0.5 Co 0.5 O₂, LiNi 0.6 Co 0.4 O₂, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O₂, LiMnO₂, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O₂, LiNi 0.8 Co 0.1 Mn 0.1 O₂, LiNi 0.6 Co 0.2 Mn 0.2 O₂, LiNi 0.9 Co 0.05 Mn 0.05 O₂, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O₂ and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O₂.

[0047] As an example, as the positive electrode active material that is the lithium-metal composite oxide represented by Chemical Formula 2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O₂, LiNi 0.8 Co 0.1 Mn 0.1 O₂ or LiNi 0.6 Co 0.2 Mn 0.2 O₂ or a combination thereof may be used alone.

[0048] Furthermore, based on 100 parts by weight of the positive electrode mixture layer, the content of the positive electrode active material can be 85 to 95 parts by weight, specifically, 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight.

[0049] In addition, the cathode mixture layer contains cathode additives represented by the following chemical formula 1.

[0050] [Chemical Formula 1]

[0051] Li p Co (1-q) M 1 q O4

[0052] In chemical formula 1, M 1 It means that at least one element is selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.

[0053] The positive electrode additive can contain excess Li and can provide Li for the lithium consumption caused by irreversible chemical and physical reactions at the negative electrode during the initial charging, thus increasing the battery's charging capacity and reducing irreversible capacity, thereby improving lifespan characteristics.

[0054] Among the additives, the positive electrode additive represented by Chemical Formula 1 has a higher lithium-ion content than nickel-containing oxides commonly used in the art. Therefore, during the initial activation of the battery, the positive electrode additive represented by Chemical Formula 1 can supplement the lithium-ion content contained in Si-based materials (e.g., Si, SiO2). q (where 0.8≤q≤2.2, etc.) The lithium consumed by irreversible chemical and physical reactions occurring at the negative electrode (where 0.8≤q≤2.2, etc.) as the negative electrode active material can significantly improve the battery's charge / discharge capacity. Furthermore, compared to iron and / or manganese oxides commonly used in the art, it exhibits superior battery stability because no side reactions due to transition metal dissolution occur during battery charging and discharging. Lithium metal oxides represented by Formula 1 may include Li6CoO4, Li6Co... 0.5 Zn 0.5 O4, Li6Co 0.7 Zn 0.3 O4, etc.

[0055] Furthermore, the cathode additive represented by chemical formula 1 can have a tetragonal crystal structure, and in the tetragonal crystal structure, the cathode additive can be contained in the P42 / nmc space group having a twisted tetrahedral structure formed by cobalt and oxygen elements.

[0056] Furthermore, based on the total weight of the positive electrode active material, the content of the positive electrode additive can be less than or equal to 5% by weight, and specifically, it can be 0.01% to 5% by weight, 0.01% to 4% by weight, 0.01% to 3% by weight, 0.01% to 2% by weight, 0.01% to 1% by weight, 0.1% to 0.9% by weight, 0.3% to 0.9% by weight, 0.2% to 0.7% by weight, 0.5% to 0.9% by weight, 0.01% to 0.5% by weight, 0.1% to 0.4% by weight, 1 to 5 parts by weight, 2 to 4 parts by weight, 0.1 to 2.5 parts by weight, 0.1 to 1 part by weight, or 0.5 to 2.5 parts by weight.

[0057] In addition to the positive electrode active material and positive electrode additives, the positive electrode mixture layer may also contain conductive materials, binders and other additives.

[0058] In this context, conductive materials can be used to improve the electrical properties of the positive electrode, and one or more carbon-based materials selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fiber can be used as the conductive material. For example, the conductive material may include acetylene black.

[0059] Furthermore, based on 100 parts by weight of the positive electrode mixture layer, the content of the conductive material can be 0.1 to 5 parts by weight, and specifically, the content can be 1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, or 1 to 3 parts by weight.

[0060] In addition, the adhesive may include at least one resin selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, and copolymers thereof. For example, the adhesive may include polyvinylidene fluoride.

[0061] Furthermore, based on 100 parts by weight of the mixture layer, the content of the adhesive can be 1 to 10 parts by weight, and specifically, the content can be 2 to 8 parts by weight, 2 to 6 parts by weight, or 2 to 4 parts by weight.

[0062] Furthermore, the positive current collector in the positive electrode can be a material with high conductivity that does not cause chemical changes in the battery. For example, stainless steel, aluminum, Ni, titanium, or calcined carbon can be used, and when using aluminum or stainless steel, aluminum or stainless steel with a surface treated with carbon, Ni, titanium, or silver can be used. Additionally, fine irregularities can be formed on the surface of the positive current collector to enhance the adhesion of the positive electrode active material, and any form of positive current collector can be used, such as a film, sheet, foil, mesh, porous body, foam, or nonwoven fabric. Furthermore, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the positive current collector can be appropriately applied in the range of 1 μm to 500 μm.

[0063] Meanwhile, the negative electrode has a negative electrode mixture layer formed by applying, drying and rolling the negative electrode active material onto the negative electrode current collector, and the negative electrode mixture layer may further selectively contain organic binder polymers, additives, etc., as in the positive electrode.

[0064] Here, the negative electrode active material may include carbon materials and Si-containing materials. Carbon materials refer to carbon materials containing carbon atoms as the main component. Carbon materials may include one or more selected from the group consisting of graphite with a fully layered crystal structure, such as natural graphite; soft carbon with a low-crystallinity layered crystal structure (graphene structure in which the hexagonal honeycomb planes of carbon are arranged in layers); hard carbon with these structures mixed with amorphous portions; artificial graphite; expanded graphite; carbon fibers; non-graphitized carbon; carbon black; acetylene black; Ketjen black; carbon nanotubes; fullerenes; activated carbon; graphene; and carbon nanotubes. More preferably, the carbon material may further include natural graphite and / or artificial graphite, and may include any one or more of graphene and carbon nanotubes together with natural graphite and / or artificial graphite. In this case, based on the total amount of 100 parts by weight of carbon material, the carbon material may include 0.1 to 10 parts by weight of graphene and / or carbon nanotubes, and more specifically, based on the total amount of 100 parts by weight of carbon material, the carbon material may include 0.1 to 5 parts by weight or 0.1 to 2 parts by weight of graphene and / or carbon nanotubes.

[0065] Furthermore, as a metallic component, Si-containing materials contain Si as the main component, and Si-containing materials can include Si, SiO, or SiO2 alone, or combinations thereof. When SiO and SiO2 are uniformly mixed or composited and contained in the negative electrode mixture layer as a silicon-containing Si material, SiO and SiO2 can be represented as silicon oxide (SiO2). x(where 1 ≤ x ≤ 2). Furthermore, when the Si-containing material has a form in which SiO particles and SiO2 particles are uniformly mixed, each particle may be in the form of crystalline particles, and when the SiO particles and SiO2 particles have a composite form, each particle may be in the form of crystalline particles or amorphous particles. In this case, based on the total amount of 100 parts by weight of silicon material, the proportion of amorphous particles ranges from 50 to 100 parts by weight, and specifically 50 to 90 parts by weight, 60 to 80 parts by weight, or 85 to 100 parts by weight. In this invention, by controlling the proportion of amorphous particles contained in the silicon material within the above range, thermal stability and flexibility can be improved without reducing the electrical performance of the electrode.

[0066] Furthermore, based on a total amount of 100 parts by weight, the negative electrode active material may comprise carbon material and Si-containing material, and may comprise 75 to 99 parts by weight of carbon material and 1 to 25 parts by weight of Si-containing material. More specifically, based on a total amount of 100 parts by weight, the negative electrode active material may comprise 80 to 95 parts by weight of carbon material and 5 to 20 parts by weight of Si-containing material, 90 to 97 parts by weight of carbon material and 3 to 10 parts by weight of Si-containing material, 85 to 92 parts by weight of carbon material and 8 to 15 parts by weight of Si-containing material, 82 to 87 parts by weight of carbon material and 13 to 18 parts by weight of Si-containing material, or 93 to 98 parts by weight of carbon material and 2 to 7 parts by weight of Si-containing material. In this invention, by adjusting the content of carbon material and Si-containing material in the negative electrode active material to the above ranges, the charging capacity per unit mass can be improved, while reducing Li consumption and irreversible capacity loss during the initial charging and discharging of the battery.

[0067] In addition, the negative electrode mixture layer may further include conductive materials, binders and other additives, as described above in the positive electrode mixture layer, as needed.

[0068] Specifically, together with the negative electrode active material, the negative electrode mixture layer may include one or more conductive materials selected from the group consisting of carbon black, acetylene black, Ketjen black, carbon fibers, graphene, and carbon nanotubes (e.g., single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs)). For example, the conductive material may include acetylene black.

[0069] Furthermore, based on 100 parts by weight of the negative electrode mixture layer, the content of the conductive material can be from 0.1 to 10 parts by weight, specifically, the content can be from 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, or 0.5 to 2 parts by weight.

[0070] In addition, the adhesive is used to adhere the negative electrode active material and can be any one or a mixture of two or more of, for example, polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polymethacrylic acid (PMAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC).

[0071] In addition, based on 100 parts by weight of the negative electrode active material, the content of the binder can be 0.5 to 5 parts by weight, specifically 0.5 to 4 parts by weight, or 1 to 3 parts by weight.

[0072] Furthermore, there are no particular limitations on the negative electrode current collector, as long as the material has high conductivity without causing chemical changes in the battery. For example, copper, stainless steel, Ni, titanium, or calcined carbon can be used for the negative electrode current collector. When using copper or stainless steel, copper or stainless steel with a surface treated with carbon, nickel, titanium, or silver can be used. Similar to the positive electrode current collector, fine irregularities can be formed on the surface of the negative electrode current collector to enhance the bonding force with the negative electrode active material. Various forms of negative electrode current collectors can be used, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics. Moreover, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately applied in the range of 1 μm to 500 μm.

[0073] Meanwhile, in the electrode assembly for lithium secondary batteries of the present invention, the average thickness of each mixed layer constituting the positive electrode and the negative electrode and / or the average area ratio between the mixed layers can be controlled within a predetermined range.

[0074] Specifically, the average thickness of the cathode mixture layer can be from 50 μm to 300 μm, more specifically, from 100 μm to 200 μm, from 80 μm to 150 μm, from 120 μm to 170 μm, from 150 μm to 300 μm, from 200 μm to 300 μm, from 150 μm to 190 μm, from 130 μm to 160 μm, from 100 μm to 150 μm, or from 110 μm to 160 μm.

[0075] Furthermore, the average thickness of the negative electrode mixture layer can be from 100 μm to 300 μm, more specifically, from 100 μm to 250 μm, from 100 μm to 200 μm, from 100 μm to 180 μm, from 100 μm to 150 μm, from 120 μm to 200 μm, from 140 μm to 200 μm, or from 140 μm to 160 μm.

[0076] Furthermore, the ratio of the average area NA of the negative electrode mixture layer to the average area PA of the positive electrode mixture layer, NA / PA, can be 1.0 to 1.1, and specifically, 1.0 to 1.08, 1.0 to 1.06, 1.0 to 1.04, 1.02 to 1.1, 1.04 to 1.1, 1.06 to 1.1, 1.02 to 1.08, or 1.04 to 1.06.

[0077] According to the present invention, by controlling the average thickness and / or average area ratio of the positive electrode mixture layer and the negative electrode mixture layer within the aforementioned range, the percentage content (CR) of the positive electrode additive contained in the positive electrode mixture layer and the negative electrode mixture layer can be easily controlled during repeated charging and discharging of the lithium secondary battery. Lip CR content percentage of Si-containing materials Si The ratio of the positive electrode mixture layer to the negative electrode mixture layer is high, and high charge / discharge capacity and efficiency can be achieved during initial charging and discharging. Specifically, when the average thickness of each of the positive and negative electrode mixture layers exceeds 300 μm, safety issues may arise during fast charging and / or overcharging of the lithium secondary battery, and when their average thicknesses are less than 50 μm and 100 μm respectively, there is a limitation on the significant reduction in charge / discharge capacity of the lithium secondary battery. Furthermore, when the average thickness of the positive electrode mixture layer is too thick and / or its average area is too wide, and thus the average area ratio NA / PA is less than 1.0, a large amount of gas is generated and expands inside the battery during charging and discharging, potentially reducing safety. When the average thickness of the negative electrode mixture layer is too thick and / or its average area is too wide, and thus the average area ratio NA / PA exceeds 1.1, the irreversible capacity increases significantly during charging and discharging of the lithium secondary battery, resulting in limitations on charge / discharge capacity and output.

[0078] Furthermore, in the electrode assembly for lithium secondary batteries of the present invention, the percentage content (CR) of the positive electrode additive is based on the total weight of the positive electrode mixture layer. Lip The percentage of Si-containing materials based on the total weight of the anode mixture layer (CR) Si The ratio between CR Lip / CR Si It can be 0.03 to 0.30, and specifically, 0.03 to 0.25, 0.03 to 0.20, 0.03 to 0.19, 0.03 to 0.15, 0.03 to 0.1, 0.05 to 0.25, 0.1 to 0.25, 0.12 to 0.2, 0.15 to 0.2, 0.15 to 0.19, 0.05 to 0.2, 0.05 to 0.18, 0.08 to 0.19, 0.09 to 0.17, 0.1 to 0.2, 0.1 to 0.15, or 0.12 to 0.18.

[0079] In this invention, the positive electrode additive and the Si-containing material contained in the positive and negative electrodes, respectively, are materials that participate in the irreversible reaction. According to this invention, the percentage of the positive electrode additive (CR) is... Lip The percentage of Si-containing materials based on the total weight of the anode mixture layer (CR) Si The ratio between CR Lip / CR Si By controlling the above range, high charge / discharge capacity and charge / discharge efficiency can be achieved during the initial charge and discharge periods.

[0080] Furthermore, a separator is inserted between the positive and negative electrodes, and an insulating film with high ion permeability and high mechanical strength is used as the separator. There are no particular limitations on the separator, as long as it is a material commonly used in the art; specifically, sheets or nonwoven fabrics made of chemically resistant and hydrophobic polypropylene, glass fiber, or polyethylene can be used as separators. In some cases, composite separators in which porous polymer substrates such as sheets or nonwoven fabrics are coated with inorganic / organic particles by an organic adhesive polymer can be used. When a solid electrolyte, such as a polymer, is used as the electrolyte, the solid electrolyte can also be used as the separator. Furthermore, the separator can have an average pore size of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.

[0081] Lithium secondary batteries

[0082] Furthermore, in one embodiment, the present invention provides a lithium secondary battery including the above-described electrode assembly.

[0083] The lithium secondary battery of the present invention can have a structure in which an electrode assembly is impregnated with an electrolyte containing a lithium salt. Specifically, the electrode assembly can be wound and housed in a cylindrical battery, a prismatic battery, or a pouch battery in the form of a jelly roll, or it can be housed in a pouch battery in a folded or stacked-folded form. Therefore, when housing the electrode assembly, the lithium secondary battery can be manufactured by injecting an electrolyte containing a lithium salt into the battery to impregnate the electrode assembly with the electrolyte.

[0084] Furthermore, the lithium salt-containing electrolyte of the present invention can be composed of an electrolyte and a lithium salt, and as the electrolyte, a non-aqueous organic solvent, an organic solid electrolyte, or an inorganic solid electrolyte can be used.

[0085] For example, as non-aqueous organic solvents, aprotic organic solvents such as N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, or ethyl propionate can be used.

[0086] For example, as organic solid electrolytes, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfides, polyvinyl alcohol (PVA), polyvinylidene fluoride, or polymers containing ion-dissociating groups can be used.

[0087] As an inorganic solid electrolyte, nitrides, halides, or sulfates of Li can be used, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, or Li3PO4-Li2S-SiS2.

[0088] Lithium salts are materials that are readily soluble in non-aqueous electrolytes. For example, LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB can be used as lithium salts. 10 Cl 10 LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lower aliphatic carboxylic acids, lithium 4-phenylborate or imide.

[0089] In addition, to improve charge / discharge characteristics and flame retardancy, substances such as pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, or aluminum trichloride can be added to the electrolyte. In some cases, to impart non-flammability, halogenated solvents such as carbon tetrachloride and trifluoroethylene can be further included, and to improve high-temperature storage characteristics, carbon dioxide gas can be further included, and fluoroethylene carbonate (FEC) and propylene sulpholone (PRS) can be further included.

[0090] Battery Module

[0091] Furthermore, in one embodiment, the present invention provides a battery module including the aforementioned secondary battery as a unit cell, and a battery pack including the battery module.

[0092] Battery packs can be used as power sources for medium to large-sized devices that require high-temperature stability, long cycle life, and high rate capability. Specific examples of medium to large-sized devices include: electric tools driven by electric motors; electric vehicles (EVs) including EVs, hybrid EVs (HEVs), and plug-in HEVs (PHEVs); electric two-wheeled vehicles including electric bicycles (E-bicycles) and electric scooters (E-scooters); electric golf carts; electric trucks; or systems for storing electricity, more specifically, for HEVs, but the invention is not limited thereto.

[0093] [Example]

[0094] The invention will be described in more detail below with reference to embodiments and experimental examples.

[0095] However, the following embodiments and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following embodiments and experimental examples.

[0096] Examples 1 to 6 and Comparative Examples 1 to 8

[0097] N-methylpyrrolidone solvent was injected into a homogeneous mixer, and in order to form a positive electrode mixture layer, LiNi, as the positive electrode active material, was weighed. 0.8 Co 0.1 Mn 0.1 O2, carbon black as a conductive material, PVdF as a binder, and Li6CoO4 as a positive electrode additive were added as shown in Tables 1 and 2 below and mixed at 3000 rpm for 60 minutes to prepare a positive electrode slurry. The prepared positive electrode slurry was applied to one surface of an aluminum current collector, dried at 100°C, and rolled to manufacture the positive electrode. In this case, the total thickness and average area of ​​the positive electrode mixture layer were 130 μm and 1260 ± 50 mm, respectively. 2 The total thickness of the manufactured positive electrode is approximately 200 μm.

[0098] In addition, natural graphite and SiO2 were prepared as negative electrode active materials. xThe negative electrode slurry is prepared in the same manner as the positive electrode slurry, using carbon black and single-walled carbon nanotubes (SWCNTs) as conductive materials (mixing ratio = 1:1 by weight) with particles of (where 1 ≤ x ≤ 2) as the conductive materials, and SBR and carboxymethyl cellulose (CMC) as binders, and referring to Tables 1 and 2 below. In this case, the graphite used in the formation of the negative electrode mixture layer is natural graphite (average particle size: 10 μm to 30 μm), and SiO₂ with an average particle size of 3 μm to 10 μm is used. x Particles. The prepared negative electrode slurry was applied to one side of the copper current collector, dried at 100°C, and rolled to manufacture the negative electrode. In this case, the total thickness and average area of ​​the negative electrode mixture layer were 150 μm and 1333 ± 50 mm, respectively. 2 The total thickness of the manufactured negative electrode is approximately 250 μm.

[0099] Here, the positive electrode additive is defined as the percentage of content (CR) based on the total weight of the positive electrode mixture layer. Lip With SiO x The percentage of particles based on the total weight of the negative electrode mixture layer (CR) Si The ratio between CR Lip / CR Si As shown in Tables 1 and 2 below.

[0100] Then, a separator made of porous polyethylene (PE) membrane (thickness: about 16 μm) is inserted between the prepared positive electrode or the prepared negative electrode, and E2DVC is injected as an electrolyte to prepare a full-cell battery.

[0101] Here, "E2DVC" is a carbonate-based electrolyte, and refers to a solution in which a mixture of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio) is mixed with lithium hexafluorophosphate (LiPF6, 1.0M) and ethylene carbonate (VC, 2% by weight).

[0102] [Table 1]

[0103]

[0104] [Table 2]

[0105]

[0106] Experimental Example

[0107] To evaluate the performance of the electrode assembly manufactured according to the present invention, the following experiments were conducted.

[0108] a) Measurement of gas emissions

[0109] For the batteries manufactured in Examples 1 to 6 and Comparative Examples 1 to 8, the amount of oxygen generated was analyzed during a single charge and discharge cycle at 25°C under 0.1C / 0.1C conditions to perform formation, and the results are shown in Table 3 below.

[0110] b) Electrical performance evaluation

[0111] The batteries manufactured in Examples 1 to 6 and Comparative Examples 1 to 8 were charged at 25°C with a charging current of 0.05C to a charging termination voltage of 4.2V to 4.25V, and then charged at 0.02V until the current density reached 0.01C. Thereafter, a single charge and discharge cycle (initial charge / discharge) was performed by discharging at a discharge current of 0.05C to a termination voltage of 2V, and the initial efficiency was calculated according to Equation 1 below by measuring the charge / discharge capacity of the battery during the charge and discharge cycle. After one charge / discharge cycle, the charge and discharge cycle was repeated 100 times with a current of 0.5C, and the charge / discharge capacity of the battery was measured in the same manner as in the initial charge / discharge cycle. After 100 charge / discharge cycles, the capacity retention rate was calculated according to Equation 2 below. The results are shown in Table 3 below.

[0112] [Equation 1]

[0113] Initial efficiency (%) = (single discharge capacity / single charge capacity) × 100

[0114] [Equation 2]

[0115] Capacity retention rate (%) = (Capacity after 100 discharge cycles / Capacity after one discharge cycle) × 100

[0116] [Table 3]

[0117]

[0118] As shown in Table 3, it can be seen that the electrode assembly of the embodiments of the present invention has the effect of improving battery performance.

[0119] Specifically, the electrode assembly of the embodiment shows that it has an initial charge / discharge capacity and efficiency of over 50.7 mAh and over 80.6%, respectively, and the battery capacity remains above 88% even after 100 cycles of repeated charging and discharging. Furthermore, in the electrode assembly for lithium secondary batteries, oxygen is generated due to the positive electrode additive according to the following reaction formula, and it has been confirmed that, compared to the electrode assembly of the comparative example, even when the same amount of positive electrode additive is included in the positive electrode mixture layer, the amount of oxygen generated in the electrode assembly of the embodiment is small.

[0120]

[0121] As can be seen from the above results, in the electrode assembly for lithium secondary batteries of the present invention, the ratio CR between the percentage of positive electrode additives and the percentage of Si-containing materials as negative electrode active materials contained in the positive electrode mixture layer and the negative electrode mixture layer is achieved. Lip / CR Si By controlling the process within a specific range, the rate and / or efficiency of reversible and irreversible reactions of lithium ions in the electrode assembly can be controlled, resulting in the following advantages: high charge / discharge capacity and charge / discharge efficiency can be achieved during the initial charge / discharge period, excellent capacity retention can be achieved during subsequent charge / discharge periods, and lithium secondary batteries including this electrode assembly can exhibit high energy density and long lifespan.

[0122] Although the invention has been described above with reference to exemplary embodiments thereof, it should be understood that those skilled in the art can devise various alternatives and modifications to the invention without departing from the spirit and scope of the invention as defined by the appended claims.

[0123] Therefore, the technical scope of the present invention should not be limited to the content described in the detailed description of this specification, but should be determined by the scope of the appended claims.

Claims

1. An electrode assembly for a lithium secondary battery, comprising: a positive electrode, wherein the positive electrode mixture layer comprises a positive electrode active material and a positive electrode additive represented by the following Chemical Formula 1; a negative electrode, wherein the negative electrode mixture layer comprises a carbon material as a negative electrode active material and a silicon (Si)-containing material; and a separator, which is disposed between the positive electrode and the negative electrode, wherein, based on 100 parts by weight of the positive electrode mixture layer, the content of the positive electrode additive is 0.01 to 5 parts by weight, and The positive electrode additive is a percentage of the total weight of the positive electrode mixture layer. Lip The percentage of Si-containing material (CR) based on the total weight of the negative electrode mixture layer Si The ratio between CR Lip / CR Si The value ranges from 0.03 to 0.

30. [Chemical Formula 1] Li p Co (1-q) M 1 q O4 In chemical formula 1, M 1 It indicates that at least one element is selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and p and q are respectively 5≤p≤7 and 0≤q≤0.

5.

2. The electrode assembly according to claim 1, wherein, The positive electrode additive is a percentage of the total weight of the positive electrode mixture layer. Lip The percentage of Si-containing material (CR) based on the total weight of the negative electrode mixture layer Si The ratio CR between Lip / CR Si The value ranges from 0.05 to 0.

20.

3. The electrode assembly according to claim 1, wherein, The positive electrode additive has a tetragonal structure with a space group of P42 / nmc.

4. The electrode assembly according to claim 1, wherein, The positive electrode active material is a lithium metal composite oxide represented by the following Chemical Formula 2: [Chemical Formula 2] Li x [Ni y Co z Mr w M 2 v ]O u In chemical formula 2, M 2 It indicates that at least one element is selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and x, y, z, w, v and u are respectively 1.0≤x≤1.30, 0≤y<0.95, 0<z≤0.5, 0<w≤0.5, 0≤v≤0.2 and 1.5≤u≤4.

5.

5. The electrode assembly according to claim 1, wherein, The carbon material comprises one or more selected from the group consisting of natural graphite, artificial graphite, graphene and carbon nanotubes.

6. The electrode assembly according to claim 5, wherein, Based on 100 parts by weight of the total amount of the carbon material, the carbon material comprises 0.1 to 10 parts by weight of one or more of graphene and carbon nanotubes.

7. The electrode assembly according to claim 1, wherein, The positive electrode mixture layer comprises 0.1 to 5 parts by weight of a conductive material based on the total weight of the positive electrode mixture layer.

8. The electrode assembly according to claim 1, wherein, The positive electrode mixture layer comprises one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fibers.

9. The electrode assembly according to claim 1, wherein, The Si-containing material comprises one or more of Si, silicon monoxide (SiO) and silicon dioxide (SiO2).

10. The electrode assembly according to claim 1, wherein: the average thickness of the positive electrode mixture layer is 50 μm to 300 μm; and the average thickness of the negative electrode mixture layer is 100 μm to 300 μm.

11. The electrode assembly according to claim 1, wherein, The average area ratio of the negative electrode mixture layer to the positive electrode mixture layer is 1.0 to 1.

1.

12. A lithium secondary battery comprising the electrode assembly according to claim 1.

Citation Information

Patent Citations

  • Method of fabricating secondary battery

    KR1020180023696A

  • Method and system for storing and providing medical records by strengthening individual's control over medical records with multi-signature smart contract on blockchain

    KR1020210067353A

  • Electrode assembly, battery cell and device comprising the same

    KR1020140113319A

  • KR20190064424A

  • KR20210055586A